The Civil Liability of Asset Managers – a Polish Perspective - Sójka, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
This paper focuses on the civil liability of asset managers in Polish law. Following the transformation of the economic system and the development of the capital market in Poland, the importance of asset management has been gradually increasing, though it remains disproportionally lower when compared to the role of collective asset management in the form of investment funds. The chief purpose of both MiFID directives is to harmonize the rules applicable to investment firms providing brokerage services in Europe, and to protect the interests of investors using brokerage services. Although the civil liability of investment firms offering brokerage services is part of what is broadly construed as investor protection, the regulations on this matter have been left to the member states’ discretion. There is no doubt that discrepancies between member states in this respect diminish the harmonizing effect of both directives. This paper sets out to determine the basic rules of civil liability of asset managers in Polish law, and present suggestions for the most common problems in this field.